(3QSGdI HOA GdJhMjO dOYhI GdMbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe MOhO YHO ehdGfG GdEeGe cJGHi Edjce eYGTQ GdENhGf GdeSJLjHjf s
(3BNQgG (B:s
(3cTakG TGajkG Ydi jO YHOg bGFe GdReGf GdfGWb HGdHjGf GdgGOi Edi MbjbI GdEjeGf JeJ hGdMeO dehdGfG hMOg hgh MSHfG hHg ai cd GdCehQ fSJYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds